Experimental and numerical investigation of the transient thermal characteristics of twisted nitinol wires in a continuous torsional refrigeration system - Zhao, Haibo; Wu, Kun (PloS one, 2022)
Twistocaloric cooling technology is a novel solid elastocaloric refrigeration to be promising alternatives to conventional compression refrigeration. The transient thermal characteristics of the twistocaloric-effect material and its cooling capacity are critical for this technology. A test rig of the continuous torsional refrigeration system (CTRS) using nitinol wires twisted by a stepping motor was built. The experimental tests show that, the surface temperatures increased as the stepping motor twisted the nitinol wires clockwise, and decreased by untwisting them counterclockwise under the stepping motor speed of 40, 45 and 45rpm. The maximum temperature rise and drop relative to the ambient temperature for the two-twisted-nitinol-wire combinations were 7.1 and 2.6°C, higher than those of 1.4 and 0.6°C for the single nitinol wire, respectively. An optimization program based on a heat conduction model was constructed to attain the potential cooling and heating capacities (PHCCs) of the nitinol wires. Then, PHCCs were introduced into the coupled flow and convective heat transfer model to predict the actual cooling and heating capacities of the CTRS. They were discovered to increase as the number of nitinol wires, the stepping motor speed, and the air velocity. The results can be referred in developing a continuous torsional refrigeration prototype.